Tanyu Tongzhi Formula Delays Atherosclerotic Plaque Progression by Promoting Alternative Macrophage Activation via PPARγ and AKT/ERK Signal Pathway in ApoE Knock-Out Mice - Ma, Lan; Dai, Xiaoce; Wu, Chenxia; Li, Mingshuang; Sheng, Hongzhuan; Mao, Wei (Frontiers in Pharmacology, 2021)
We previously demonstrated that the Tanyu Tongzhi Formula (TTF) significantly alleviated the clinical symptoms of patients with coronary heart disease and lowered serum lipid and inflammatory factor levels in patients with coronary heart disease and atherosclerosis model rats. However, the mechanism underlying TTF remains unknown. In this study, we examined the effect of TTF on atherosclerotic plaques in ApoE-/- mice and underlying mechanisms involved in macrophage polarization. Sixty male ApoE-/- mice were randomly divided into four groups. Mice in the control group were fed a regular diet, whereas experimental mice were fed a high-fat diet and received either saline (HFD group) or TTF at concentrations of 0.60 (TTF-L group) or 2.25 g/ml (TTF-H group) by daily oral gavage for 16 weeks. In the TTF-L and TTF-H groups, the levels of serum cholesterol, triglyceride, interleukin (IL)-1β, IL-6, and tumor necrosis factor (TNF)-α were decreased, lipid content was significantly decreased, and percentage area of collagen/lipid increased in atherosclerotic plaque compared to in the HFD group. Moreover, we found TTF promoted the expression of alternative macrophage markers (Fizz1, Arg1, and Mrc) and suppressed the expression of M1 macrophage markers (TNF-α, IL-1β, and IL-6) by regulating peroxisome proliferator-activated receptor γ (PPARγ) expression and AKT/extracellular signal-regulated kinase (ERK) activation. We further investigated whether alternative macrophage was reduced when PPARγ was inhibited or the AKT/ERK signaling pathway was activated. TTF delayed atherosclerotic plaque progression by promoting alternative macrophage activation through increasing PPARγ expression and inhibiting AKT/ERK phosphorylation, providing a theoretical basis for its clinical application.